2011
DOI: 10.1159/000327298
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro Effects of Advanced Glycation End Products on Basophil Functions

Abstract: Background: Basophils are thought to play pivotal roles in the pathogenesis of allergic reactions, but their roles in inflammation associated with systemic abnormalities such as metabolic disorders remain largely unknown. Advanced glycation end products (AGEs) are potentially important substances produced in high-glucose disease conditions. In this in vitro study, we investigated whether the biological functions of human basophils can be influenced by AGEs. Methods: We analyzed the effects of AGEs on various f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
6
12
0
Order By: Relevance
“…Activation of RAGE is associated with increased cell survival of eosinophils stimulated with S100B, a RAGE ligand, over a period of 48 hours, which is similar to our findings in the same experimental period 5 . The role of RAGE activation in increased cell survival is also suggested by a report of a positive correlation between the expression of RAGE and cell viability in neoplastic pancreatic cells 8 . Inhibition of p38 MAPK did not modulate apoptosis of T lymphocytes and monocytes in the presence and absence of RAGE and TLR4 agonists, and similar findings are reported in literature in T lymphocytes and monocytes 30 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Activation of RAGE is associated with increased cell survival of eosinophils stimulated with S100B, a RAGE ligand, over a period of 48 hours, which is similar to our findings in the same experimental period 5 . The role of RAGE activation in increased cell survival is also suggested by a report of a positive correlation between the expression of RAGE and cell viability in neoplastic pancreatic cells 8 . Inhibition of p38 MAPK did not modulate apoptosis of T lymphocytes and monocytes in the presence and absence of RAGE and TLR4 agonists, and similar findings are reported in literature in T lymphocytes and monocytes 30 .…”
Section: Discussionmentioning
confidence: 80%
“…However, the experimental period was 5 days, as opposed to 1, 2 and 3 days in our study. Lower concentrations of AGE-BSA (1, 10 and 100 ug/mL) are not capable of inducing apoptosis in human basophils, which was only observed with high concentrations (1,000 ug/mL) at 48 h 8 . Activation of RAGE is associated with increased cell survival of eosinophils stimulated with S100B, a RAGE ligand, over a period of 48 hours, which is similar to our findings in the same experimental period 5 .…”
Section: Discussionmentioning
confidence: 87%
“…In animals, it has been shown that dietary AGE-BSA results in elevation of IL-6 in their blood serum (33). AGEs also induced IL-6 and IL-8 secretion from human basophil cells (34) and from osteoarthritis chondrocytes by the activation of nuclear factor-jB (NF-jB) (35). Consistent with these previous reports, we observed that the incubation of HGFs with 200 lg/mL of AGEs (33) could significantly increase their production of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is highly expressed on DCs, macrophages, T lymphocytes, and B cells, as well as mast cells and basophils. 32,[46][47][48][49] AGEs binding to the RAGE receptor activate mast cells and induce exocytosis of histamine and generation of oxidative stress products in a dose-dependent mechanism (within 20 seconds). 49 T-cell activation and proliferation is dependent on RAGE activation, 25 and DCs require RAGE signaling for migration to lymph nodes in response to an antigen.…”
Section: Western Diet High In Ages Can Induce Alarmin Signalingmentioning
confidence: 99%